Competition and training strategies for developing world class 200- and 400-m individual medley swimmers - González Ravé, J. M.; Del Castillo, J. A.; Santos del Cero, J.; Hermosilla, F.; Pyne, D. (Journal of Human Kinetics, 2023)
Swimming performance achieved in 50-m, 100-m and 200-m events in each swimming stroke can have an influence on the final performance in individual medley (IM) events. We attempted to quantify the relative contributions of performance in individual stroke events to top-10 world ranked IM competition performance. We examined competition results of top-10 world ranked IM swimmers (90 males and 90 females) between 2012 and 2018. A general linear model was developed to examine association between the 200-m and 400-mIM and predictor variables of competition performance in other 50-m, 100-m, and 200-m events. The main predictor variable for 200-mIM medalist status was having scored more than 900 FINA points in at least one 100-m event. Scoring more than 800 FINA points in at least two 200-mIM events, and more than 900 FINA points in at least one 100-m event, was important for success in the 400-mIM. Top-10 world ranked 200-mIM and 400-mIM swimmers require a world class standard in one or more individual stroke event(s)